Divine service? Judaism and Israel's armed forces - Cohen, Stuart 1946- (Religion and international security, 2013)
Soldiering, which for almost two millennia was almost entirely foreign to Jewish thought and practice, has by virtue of universal conscription become a rite of passage to citizenship in the Jewish state. For practicing orthodox Jews in Israel that change generates dilemmas that are intellectual as well as behavioural.